Improving Mathematics Learning Outcomes of Elementary School Students with the Direct Learning Method (An Experimental Study in South Papua) - Adrianus Tambing Bontong; Martha Betaubun; Karlina Wong Lieung; Hendrika Walten (Universitas Muhammadiyah Enrekang, 2023)
The difficulty of learning mathematics is an obstacle problem in everyday life so it needs to be mastered properly, but most students consider mathematics to be a difficult subject, especially grade II students of SD Negeri 2 Merauke, the perception that mathematics is a difficult subject is reinforced by low mathematics learning results. Therefore, the purpose of this study is to improve students' mathematics learning outcomes using direct learning methods. The method used in this study is the quantitative method with analysis using the mean score. The population in this study was SD Negeri 2 Merauke, with a total sample of 23 students in grade II. The data in this study were obtained from observations and tests. The results showed that, the students' pre-test results were 59.13% while the results of the post-test were 82.08%. Because of this, it can be claimed that the direct learning method can improve the mathematics learning outcomes of grade II students of SD Negeri 2 Merauke, South Papua. Given the importance of mastering mathematics well, teachers should teach mathematics in a variety that is in accordance with the theory of learning mathematics accompanied by the use of teaching aids / media that can increase student learning motivation.